1989
DOI: 10.1099/00221287-135-4-751
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Scytalidium thermophilum in Mushroom Compost and Stimulatory Effects on Growth Rate and Yield of Agaricus bisporus

Abstract: Mycelial growth of Agaricus bisporus on sterilized compost is strongly stimulated by preincubating the compost with the thermophilic fungus Scytalidium thermophilum. This stimulatory effect is not species specific, for either A . bisporus or S. thermophilum. Normal mushroom compost is almost completely colonized with S. thermophilum. In experimental composts a positive relation was found between the logarithm of mushroom yield of A . bisporus and the density of S. thermophilum. S. thermophilum provides for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 12 publications
1
44
0
Order By: Relevance
“…Streptomyces has important ecological roles in decomposition of organic matters such as plant wastes, manure and organic fertilizers by using keratinase and chitinase as nitrogen and carbon sources [33] and cellulose [34]. Hopkins et al [35] and Motr [36] used isolated Streptomyces in the decomposing biotechnology because it is capable to use and utilize lignin and cellulosic matters as carbon source with inhibitory activity against pathogens and undesirable fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Streptomyces has important ecological roles in decomposition of organic matters such as plant wastes, manure and organic fertilizers by using keratinase and chitinase as nitrogen and carbon sources [33] and cellulose [34]. Hopkins et al [35] and Motr [36] used isolated Streptomyces in the decomposing biotechnology because it is capable to use and utilize lignin and cellulosic matters as carbon source with inhibitory activity against pathogens and undesirable fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Among these microorganisms, thermophilic fungi appear to be important for compost selectivity. Torula thermophila and Humicola grisea var thermoidea (synonyms of Scytalidium thermophilum) (Straatsma et al, 1991), have been shown to be the most abundant thermophilic fungi in mushroom compost (Ross and Harris, 1983;Straatsma et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore application of tebuconazol could be a limiting factor for the use of straw for compost preparation and mushroom cultivation. There are no specific data on fungicide degradation during mushroom composting; but in a review, Miller (1991) (Ross and Harris, 1983;Fermor and Grant, 1985;Gandy, 1985;Straatsma et al, 1989). Savoie et al (1992) …”
Section: Introductionmentioning
confidence: 99%
“…The composting process was also improved when it was discovered that conditioning at a temperature between 50º C and 60º C was important not only to eliminate pests, illnesses and contaminants, but also for guaranteeing compost quality and, consequently, making mushroom cultivation more productive (Flegg et al, 1986). As a result, much research has been aimed at understanding the role of microorganisms involved in the composting process (Fergus, 1964;Straatsma et al, 1989Straatsma et al, , 1994Epstein, 1997;Salar & Aneja, 2007a,b). These studies have demonstrated that an appropriate microbial succession is essential for obtaining a selective compost of good quality.…”
Section: "Champignon De Paris" (Agaricus Bisporus)mentioning
confidence: 99%